Analisis Victimology dalam Faktor Sosial Serta Perlindungan Hukum Terhadap Korban Bullying - Maulana Malik Ibrahim; Vania Elvina; Arif Pratama Kuswanto; Kayladiva Hasan (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2025)
Bullying is an act of physical or psychological violence that can have long-term effects on its victims. In the context of legal protection, Law No. 35 of 2014 on Child Protection serves as the legal foundation for protecting children from all forms of violence, including bullying. This legal protection includes both preventive and repressive measures against perpetrators, as well as the provision of facilities for the recovery of victims.Moreover, social factors such as cultural norms, family environment, and peer interactions often exacerbate the impact of bullying. Stigma and discrimination against victims, which frequently arise due to a lack of public awareness, can worsen their psychological condition and hinder the recovery process.This study aims to analyze the social and legal impacts of bullying on victims and highlight the importance of more effective legal protection in reducing the prevalence of bullying in society.